Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376781
|View full text |Cite
|
Sign up to set email alerts
|

Sara, the Lecturer: Improving Learning in Online Education with a Scaffolding-Based Conversational Agent

Abstract: Enrollment in online courses has sharply increased in higher education. Although online education can be scaled to large audiences, the lack of interaction between educators and learners is difficult to replace and remains a primary challenge in the field. Conversational agents may alleviate this problem by engaging in natural interaction and by scaffolding learners' understanding similarly to educators. However, whether this approach can also be used to enrich online video lectures has largely remained unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…PCAs are software programs that communicate with users through natural language interaction interfaces [57,79]. They have been successfully used to adaptively support learners to conduct a task by mimicking the gold standard of human tutors, e.g., for programming tasks [83], mathematical skills [8] as well as for learning factual knowledge [53]. Due to developments in domains such as Natural Language Processing (NLP) and Machine Learning (ML), PCAs are also becoming increasingly valuable for more creative and harder to grasp skills such as argumentation.…”
Section: Introductionmentioning
confidence: 99%
“…PCAs are software programs that communicate with users through natural language interaction interfaces [57,79]. They have been successfully used to adaptively support learners to conduct a task by mimicking the gold standard of human tutors, e.g., for programming tasks [83], mathematical skills [8] as well as for learning factual knowledge [53]. Due to developments in domains such as Natural Language Processing (NLP) and Machine Learning (ML), PCAs are also becoming increasingly valuable for more creative and harder to grasp skills such as argumentation.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, conversational interfaces such as Apple's Siri, Microsoft's Cortana, Amazon's Alexa, or Google's Assistant are ubiquitous, and they are used in several areas, such as customer service, health care or education (Janssen et al, 2020). For example, research by Winkler et al (2020b), Wambsganss et al (2021 and (Winkler et al 2021) has shown that the use of SPAs in educational settings has a positive impact on different learning outcomes, such as problem solving or argumentation skills. Further, research in this stream also analyzes how HIS can be employed to foster innovation in various value creation processes (Elshan & Ebel, 2020;Elshan et al, 2021;Engel & Ebel, 2019).…”
Section: Design Of Hybrid Intelligence Systemsmentioning
confidence: 99%
“…Based on previous research, chatbots show promise as a novel way to provide learning-related [28,46] and health-related support [19]. In the present study, we take an integrative approach to target all student concerns related to studies, well-being, and other issues.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…In the educational context, chatbots have been used, for example, in admissions [34], elective course selection [12], helping students in their campus life [13], language learning [8] and instructional scaffolding [46]. One prominent use case for chatbots in education is a virtual student advisor who helps students with studies, wellbeing, and other issues.…”
Section: Introductionmentioning
confidence: 99%